2004
DOI: 10.1021/jo0487956
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Generation of Highly Destabilized Vinyl Cations:  The Effects of α- and β-Trifluoromethyl versus α- and β-Methyl Substituents

Abstract: The photochemical reactions in methanol of the vinylic halides 1-4, halostyrenes with a methyl or a trifluoromethyl substituent at the alpha- or beta-position, have been investigated quantitatively. Next to E/Z isomerization, the reactions are formation of vinyl radicals, leading to reductive dehalogenation products, and formation of vinyl cations, leading to elimination, nucleophilic substitution, and rearrangement products. The vinyl cations are parts of tight ion pairs with halide as the counterion. The eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Irradiations of the α‐methylstyrene bromides 1 , and the α‐fluorostyrene bromides 2 in methanol yield vinyl radical‐derived products. Homolysis is a minor reaction pathway for 1 ,17 but is effectively the only bond rupture process observed for 2 21. In Table 1 the quantum yields of formation of the two reductively dehalogenated isomers c and d and their ratio observed in the irradiation of the E ‐ and Z ‐isomers of 1 and 2 are summarized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiations of the α‐methylstyrene bromides 1 , and the α‐fluorostyrene bromides 2 in methanol yield vinyl radical‐derived products. Homolysis is a minor reaction pathway for 1 ,17 but is effectively the only bond rupture process observed for 2 21. In Table 1 the quantum yields of formation of the two reductively dehalogenated isomers c and d and their ratio observed in the irradiation of the E ‐ and Z ‐isomers of 1 and 2 are summarized.…”
Section: Resultsmentioning
confidence: 99%
“…The E ‐ and Z ‐isomers were separated using column chromatography (silica/petroleum ether, boiling range 40–60 °C) in >98 % purity. Their spectroscopic characterizations are reported in ref 17…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8) Further reduction using lithium aluminum hydride as a reductant produced alcohol 9, which was oxidized to give aldehyde 10 using PCC. 19) Then, compound 10 reacted with methylidene triphenyl phosphorane in the presence of potassium tert-butoxide to synthesize compound 11 via the Witting reaction, 20) subsequent addition reaction with bromine to afford bromide 12. The key intermediate 13 were carried out in various conditions as shown in Fig.…”
Section: Chemistrymentioning
confidence: 99%
“…However, an α-monofluoromethyl carbocation, 1-fluoro-2-propylium cation (CH 3 CH + CH 2 F), was characterized as a transient intermediate in the gas phase, 6 and an extremely unstable α-trifluoromethylvinyl cation, 3,3,3-trifluoro-1-phenyl-2-propenium cation, was generated through a photochemical reaction. 7 We have earlier demonstrated that the π-delocalized, α-trifluoromethylallyl cations 1-3, formed in superacidic media at low temperatures, have relatively low C 1 -C 2 rotational barriers of about 9 kcal/mol, implying that the positive charge is substantially localized on the tertiary carbon (C 3 ). 3 That is, the positive charge is disfavored at the C 1 due to the strong electron-withdrawing inductive effect of the trifluoromethyl group.…”
Section: Introductionmentioning
confidence: 99%